Malaysian instructors' assessment beliefs in tertiary ESL classrooms - Elshawa, Niveen R. M.; Abdullah, Ain Nadzimah; Md Rashid, Sabariah (Australian International Academic Centre, 2017)
Language assessment can be a valuable tool for providing information regarding language teaching. Given the importance of assessment that has undergone much change, there are important issues that warrant investigation, particularly those related to language instructors. Understanding the assessment beliefs of ESL instructors, especially at the tertiary level, is important since it can help improve the quality of assessment practices as well. Therefore, this study investigated English language instructors’ assessment beliefs in the Malaysian context. This study adopted a cross-sectional research design. The survey method was utilized to collect data from six Malaysian universities using a purposive sampling strategy. English language instructors (n=83) were selected via purposive sampling for the study. Findings of the study revealed that English language instructors believed that the purpose of assessment was to improve teaching and learning. Regarding the assessment beliefs that are related to the assessment purposes, analyses of data showed that the items that received the highest percentage of agreement were diagnosing strength and weaknesses in students, providing information about students’ progress and providing feedback to students as they learn, respectively. Although they reported using both formal and informal assessment of their students’ work, English language instructors relied heavily on paper and pencil assessment while giving more weightage on formative assessment. The majority of English language instructors reported employing marking schemes for the courses they taught, carrying out sample marking and providing feedback. Finally, English language instructors reported using different types of assessments for every language skill taught in their language unit/center. The findings highlight the fact that English instructors should be more empowered in their role as the assessors of students. Their knowledge about what, how, when to assess should be developed through long professional development courses; one-shot workshops or seminars would not be enough to improve instructors’ assessment literacy.